1977
DOI: 10.1088/0031-9155/22/2/001
|View full text |Cite
|
Sign up to set email alerts
|

A determination by an analysis of X-ray attenuation in aluminium of the intensity distribution at its point of origin in a thick tungsten target of bremsstrahlung excited by constant potentials of 60-140 kV

Abstract: A recently described, computer aided method of attenuation analysis has been applied to free-air chamber measurements of the attenuation by up to 30mm A1 of the exposure rate of a narrow beam of X-radiation excited at a thick W target in a Be window tube by constant potentials of 60, 80, 100, 120 and 140 kV. It has been shown that the general characteristics of the intensity distributions of the bremsstahlung at its point of origin within the target found by an earlier analysis are fully confirmed but that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Unsworth and Greening ͑1970͒ had some success with developing a thick target model, 5 based on Kramers work, and Soole calculated a target attenuation correction later in that decade, showing a more empirical approach to the treatment of the bremsstrahlung cross section. 6,7 In 1978, Birch and Marshall helped towards making spectral calculation a common tool in medical physics with an approach which has come to be known as semiempirical. 8 In the face of discrepancies between theoretical calculations and observation, following the tack of Soole, they abandoned derived formulas for the bremsstrahlung cross section and modeled this using an empirical function.…”
Section: Introductionmentioning
confidence: 99%
“…Unsworth and Greening ͑1970͒ had some success with developing a thick target model, 5 based on Kramers work, and Soole calculated a target attenuation correction later in that decade, showing a more empirical approach to the treatment of the bremsstrahlung cross section. 6,7 In 1978, Birch and Marshall helped towards making spectral calculation a common tool in medical physics with an approach which has come to be known as semiempirical. 8 In the face of discrepancies between theoretical calculations and observation, following the tack of Soole, they abandoned derived formulas for the bremsstrahlung cross section and modeled this using an empirical function.…”
Section: Introductionmentioning
confidence: 99%
“…Kramers (1923) assumed that the original differential energy intensity was constant, and did not allow for the target absorption, the two parameters more or less masking each other as noted by Soole (1972). Soole (1977) determined the varying differential energy intensity by matching data generated by Kramers' theory, modified to allow for target absorption, with attenuation measurements. However, Soole did not present spectra calculated using this theory, and on doing so we found that the target attenuation was too great, indicated by too large a drop a t the tungsten K-edge a t higher voltages when compared to measured spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Silberstein 30,31 recognized the relationship between the attenuation curve, measured with absorbers of various thicknesses, and the energy spectrum. Others subsequently applied different methods of numerical analysis of the attenuation data, including Laplace transform techniques, 32-36 iterative methods, 37-40 modeling, 41,42 and matrix manipulation. 43 Application of catalog or theoretical spectral data is valid only if the x-ray system is well characterized.…”
Section: B Methods To Calculate Energy Spectramentioning
confidence: 99%